Predictors of research performance and mediation influence of work engagement among academics at selected Malaysian research universities - Tauhed, Siti Zainab (2018)
Research performance among academics at Malaysian Research Universities is very significant in the present competitive academic world. This is based on the fact that university’s ranking that is mainly based on the research activities and outputs, plays a significant role in determining the standing and reputation of a university. Therefore, studies to understand the phenomena about research performance of academics remains pertinent, especially from the non-western perspective. In the context of job performance, past empirical studies have substantiated that work engagement mediates the relationship between job performance and its predictors. However, work engagement has less been studied in the context of academics’ work, particularly in research. Research performance of academics was theorized using Kahn’s Theory of Personal Engagement at Work and Job Demands-Resources Theory. These theories highlight that works environment which includes organizational factors (organizational culture and transformational leadership), work resources (task significance and networking), and individual factors (individual effort, time management, and professional development) all of which explain individual research performance. Thus, this study aims were to determine the influence of these factors on academics’ research performance and the mediating influence of work engagement between the predictors and research performance. This study adopted a quantitative research paradigm using descriptive and correlational research methodology. Data were collected using cross-sectional study approach. The structured questionnaire was employed to collect data from 381 academics from grade 51/52 up to VK7 at the selected Malaysian Research Universities. They were chosen using the proportionate stratified random sampling procedure. Structural Equation Modeling was employed to examine the structural model of the study. The descriptive statistics of this study showed that the research performance of academics at MRUs is not promising. Results from the direct effect analysis showed that individual effort and professional development influenced significantly to research performance of academics. These findings indicate that individual factors are significant predictors of research performance. In addition, organizational culture and transformational leadership significantly influenced work engagement. This shows that organizational factors are an important aspect in explaining work engagement. This study also found that work engagement did not mediate the relationship between research performance and its predictors. This study did not support Kahn’s Theory of Personal engagement at Work and Job Demands-Resources Theory in explaining organizational factors and work resources as predictors of academics’ job performance in research. The study concluded that job performance is explained by different factors according to the nature of work. Research performance of academics in this study needs further attention and it is the function of individual factors. On the other hand, organizational factors are important in developing an engaged workforce. However, this study also concluded that work engagement did not have a mediation influence between its predictors and research performance. The study broadens the concept of research performance measures which mainly dominated by the number of publications and citations. This study also offers new insight for the Human Resource Development Practitioners related to academics’ job performance in research which has been understudied. In terms of practice, individual effort and professional development need to become an important strategy to improve research performance of academics.